Dignity, families, and family therapy - Todd M. Edwards; Jo Ellen Patterson; James L. Griffith (Academia Mental Health & Well-Being)
Dignity has been described as an individual and social construct. Dignity is the enactment of identity in the social space of a community, where what matters is how the person perceives the community to be responding to this expression of identity. It is how individuals perceive their worth and belonging within their community. The loss of dignity can lead to feelings of shame and isolation, while its restoration brings pride and honor. Families play a key role in preserving dignity to reinforce care and mutual respect. In this paper, we link dignity to concepts in systemic family therapy and describe family interventions to preserve and restore dignity.